Deteksi Bakteri Patogen Salmonella typhi pada Sayuran Mentah Menggunakan Metode nested Polymerase Chain Reaction - Idar Idar; Shinta Kusumawardhani; Mia Tria Novianti (Al-Kimia, 2018)
Salmonella typhi (S. typhi) infection is a zoonotic infection and known as salmonellosis. In the human body, salmonellosis causes an increase in high body temperature or known as typhoid fever that cause high morbidity and mortality in developing countries, especially Indonesia. It was found that out of 22 million cases of typhoid fever, 200 thousand of them ended in death. S. typhi often contaminates food that was consumed raw or not perfectly cooked, for example meat, eggs, dairy products, fruits and vegetables. The conventional method for detecting these bacteria is culture method which time consuming and need BSL 2  facilities. PCR was one of DNA based detection method that could overcome the culture method weakness. In this study conducted detection of Salmonella bacteria in raw vegetables which are usually consumed as fresh by using nested PCR method. The detection procedures were sample preparation; bacterial DNA isolation; amplification by using two sets of primer, ST1-ST2 in first round PCR and ST3-ST4 in second round PCR; and the characterization by using agarose electrophoresis. The results indicated that two of nine raw vegetables, tomatos and cabbages have been contaminated with Salmonella. We conclude that nested PCR could detect Salmonella contamination in raw vegetables.